Self-Identification of Homestay Management Problems and Canvas Business Model - Majidah, Majidah; Cahyaningsih, Cahyaningsih; Saraswati, Rr Sri; Inawati, Wahdan Arum (Journal of Innovation and Community Engagement, 2021)
Laksana Village is in Ibun Sub-District, Bandung District. Geographically, Laksana Village is close to the Kamojang Tourism area, which is the leading tourism destination in Bandung District. The village has the potential for tourism development. To support the tourism development program, there are several homestays. However, it was found that many tourists spent the night outside the Laksana Village area. Another problem faced by homestay managers is the difficulty in determining homestay tariff. This Community Service (CS) activity aims to explore the problems faced by homestay managers through self-identification of problems using the Community Based Participatory Research method. The results of the self-identification became the basis for the CS Team to map the nine elements of the canvas business model. The cost structure becomes a priority scale to be handled in order to solve the tariff determination problem and is expected to increase the value proposition. This CS activity specifically resulted in self-identification of problems and a business canvas model for homestay management.